Belajar Sambil Berdampak Pada Penugasan KM 4, SMP Kristen 3 Kalabahi - Isdarmayanti Isdarmayanti; Jon Idrison Molina; Landerius Maro; Jeni Marianti Loban (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The Teaching Campus Program provides opportunities for students to learn outside the classroom by becoming teacher partners in the learning process at the educational level. Through this program the role of students is needed to provide better learning to schools and hone creativity. In addition, during the assignment, students are also given the task of assisting the administration at the school where the assignment is. As for what we do on the sidelines of the activities that we program, we also help with school administration in accordance with directions from the school and school operators.